Innovation management of MTs Muhammadiyah Boarding School (MBS) Magetan - Suwardi; Sedya Santosa (Riviera Publishing, 2026)
This research focuses on the management innovations of MTs Muhammadiyah Boarding School (MBS) Magetan, a pioneering institution that implements a pesantren-based education system by housing students in dormitories. The culture of innovation within the Muhammadiyah education environment represents an effort to improve the quality of School-Based Management (SBM) in response to government policy demands and developments in science and technology. This research aims to examine the management innovations carried out by MBS Magetan in improving school quality through SBM, within the context of advancing science and technology. The study employs a qualitative method, with data collected through observation and documentation and analyzed using a descriptive-analytical approach. The findings reveal three key dimensions. First, school culture is composed of: (a) core values that are collectively upheld, and (b) those values translated into a shared culture expressed through symbols and activities. Second, the school as a learning organization encompasses: (a) personal mastery, (b) mental models, (c) shared vision, (d) team learning, and (e) systems thinking. Third, innovation in SBM is implemented through: (a) School-Based Management and Integrated Quality Management, (b) student-centered active learning, and (c) the Quantum Teaching method. The management innovations carried out by MBS have fostered good discipline, orderly administration, and consistent leadership, while in the area of teaching and learning, they have cultivated a cooperative, active, creative, and engaging learning atmosphere.